Belgesel Sinemanın Alternatif Dağıtım Ve Gösterim Olanağı Olarak İnternet - Erkılıç, Hakan; Toprak, Ayşe Gül (The Turkish Online Journal of Design Art and Communication, 2012)
distribution and release channels .With digital technology, non-fiction film obtains various and free field than ever before. Making low cost, speed, easy access possible ; digital technology , by this way makes the differences not only changing production mode of films but also meeting style to the audience. DVD and VoD (video on demand) systems varies vieweing platforms of consumer. Documentary films which can’t find the chance to be released in movie theatres have the opportunity of meeting the audience through web sites here after. So having a film (watching or purchasing a film) through internet carries documentary beyond nation –state borders.In this notice, documentary film’s usage of web based systems as an alternative distribution and release opportunity is going to be argued .This system’s features such as streaming, VoD, DVD sales, information sharing will be evaluated too. Also whether this tendency in the world will be an alternative or not in documentary production and distribution in Turkey is going to be interrogated.
Keywords: Documentary Cinema; Distribution; Release; Video on Demand; Belgesel Sinema; Dağıtım; Serbest Bırakma